Identification of chemical components of rosemary essential oil (Rosmarinus officinalis L.) from organic crops in the high Andean zone - Pulido Arango, Ana María; Riveros Loaiza, Luis Miguel; Rodriguez Cabra, Javier Leonardo (Revista Colombiana de Investigaciones Agroindustriales, 2018)
For the present study, rosemary (Rosmarinus officinalis L. var. Israeli) samples were collected from organic crops located in the high Andean area of Colombia for 6 and 24 months of transplanted, they were submitted to extraction of essential oil by steam distillation in Prototype equipment made of stainless steel. These oils were analyzed using GC-MS, there were determine the chemical components present in these samples and the relative proportion. In order to know the existence of variations in the composition of the oil obtained in said equipment, the simultaneous extractions were carried out in the laboratory with a structure of the same characteristics but made of glass. These samples were analyzed by GC-MS and therefore, it was obtained that the oils extracted in the prototype are composed in greater amount by monoterpenes and oxygenated monoterpenes, contrary to those obtained in the laboratory, where most were oxygenated monoterpenes. Eucalyptol, α-pinene, camphor, β-caryophyllene, bornyl acetate, camphene, β-pinene, limonene, phellandrene and γ-terpinene were the major compounds in all samples analyzed, but in oils extracted in the prototype for plant of 24 months, the majority compound was α-pinene, unlike the one obtained in the laboratory for the same sample, where the compound with the highest presence was Eucalyptol. As for camphor, β-careophilene and bornyl acetate, showed a decrease in their presence in the oils extracted in the prototype in plant of 24 and 6 months, contrary to camphene, β-pinene and limonene, that increased their relative concentration in the oils extracted in the prototype, showing differences in oils extracted in each of the study equipment.